How to Reduce Mortality in crossbred calves - Upadhyay, Deepak; Gaur, G K; Mishra, Madhu; Singh, Mukesh; Bharti, P K (Indian Farming, 2017)
To reduce mortality in crossbred calves, adequate attention is required on nutrition, health care, housing, medication and inbreeding. Many diseases of newborn calves can be controlled by well-designed health management programs including thecare and housing of dam during periparturient period, standardoperating procedures for calving process and application of properpreventive measures (including sound nutritional programs). The five C’s (Colostrum, Cleanliness, Comfort, Calories and Consistency) provide an effective formula for managing the young dairy calf and to reduce the mortality within acceptable limit.